Beckman's New Combustion Efficiency System Directly Controls Process Heater Damper, Saves Energy and Reduces Pollution - Eastman, Elke (1981)
The press release describes the Model CE-1000 Combustion Efficiency System unveiled at the ISA show in Anaheim.
Keywords: Combustion; Gases--Analysis; Scientific apparatus and instruments; Pascal (Computer program language); Beckman Instruments, Inc.